(untitled) (REVUE DES SCIENCES DE LA SANTE, 2026)
Malaria remains a major public health challenge in sub-Saharan Africa, where local communities continue to rely extensively on plant resources for protection against mosquito vectors. This study aimed to document the plant species used against mosquitoes in the Madimba Territory (Kongo Central Province, Democratic Republic of the Congo), assess their ethnobotanical importance, and analyze floristic variations among local communities. Semi-structured ethnobotanical surveys were conducted between April and December 2025 among 385 informants selected using the snowball sampling method. The collected data were analyzed using ethnobotanical indices, descriptive statistics, Fisher’s exact test, and the Jaccard similarity index. A total of 28 plant species belonging to 17 botanical families were recorded, with Fabaceae and Annonaceae being the most represented families. Phanerophytes dominated the recorded flora (75%), while trees constituted the predominant growth form (46%). Leaves were the most frequently used plant part (74.29% of citations), and fumigation was the principal mode of application (66.82%). Ethnobotanical knowledge varied significantly according to respondents’ sex and age (p < 0.0001), but not according to educational level (p > 0.05). The most frequently cited species were Tephrosia vogelii (19.71%) and Nicotiana tabacum (19.23%), followed by Cananga odorata (10.81%) and Cinnamomum verum (10.09%). Repellent plants accounted for 67.85% of the recorded species, whereas insecticidal plants represented 10.71%. Similarity analyses revealed moderate variation in the use of anti-mosquito plants among the studied tribes and villages, although no statistically significant differences were observed between groups (p > 0.05). These findings highlight the importance of indigenous knowledge in mosquito control and identify several promising plant species that could serve as potential sources of environmentally friendly alternatives to synthetic insecticides.